PERENCANAAN PENGEMBANGAN RUANG TERBUKA HIJAU SEBAGAI AREA PUBLIK - Bayu Hendarmoko; GunGun Gumila; Evi Priyanti; Dadan Kurniansyah (Journal Publicuho, 2021)
When discussing Green Open Space (RTH), of course its existence is something that is underestimated by most people even by the district/city government. This is because the mindset of the community and the government that considers the development of Green Open Spaces is not too important is carried out because of the lack of feedback provided by Green Open Spaces to the community and government so that the land of a Regency / City area is overcrowded by other infrastructure developments plus other with the increase in population, resulting in the need for new Green Open Spaces in their minds. The research method used is a qualitative approach with data collection techniques through literature or literature studies.This was only realized because of the community's need for a place to release the fatigue that afflicts due to the many demands from work, the worsening of air quality in a Regency/City area as a result of the rise of industry and motorized vehicles which make the air increasingly polluted by air pollution, and also the lack of land for accommodate water when it rains which makes many areas flooded when it rains because of the lack of water catchment areas. Keywords: Development Planning; Green Open Space; Regulation   AbstrakBila membahas Ruang Terbuka Hijau (RTH) tentunya keberadaannya bagaikan sesuatu yang dianggap remeh oleh kebanyakan orang bahkan oleh pemerintah kabupaten/kota. Hal ini dikarenakan pola pikir dari masyarakat dan pemernitah yang menganggap pembangunan Ruang Terbuka Hijau tidaklah terlalu penting itu dillakukan  karena kurangnya input balik yang diberikan oleh Ruang Terbuka Hijau kepada masyarakat maupun pemerintahan sehingga membuat lahan dari suatu wilayah Kabupaten/Kota penuh sesak oleh pembangunan infrastruktur lainnya ditambah pula dengan bertambahnya jumlah penduduk sehingga mengakibatkan kebutuhan akan Ruang Terbuka Hijau baru terpikirkan oleh mereka.Metode penelitian yang digunakan adalah pendekatan kualitatif dengan teknik pengumpulan data melalui studi literatur atau kepustakaan. Hal ini baru disadari karena kebutuhan masyarakat akan tempat untuk melepas kepenatan yang menimpa karena banyaknya tunututan dari pekerjaan, bertambah buruknya kualitas udara disuatu wilayah Kabupaten/Kota imbas dari maraknya industri dan kendaraan bermotor yang membuat udara semakin tercemar oleh polusi udara, dan juga kurangnya lahan untuk menampung air ketika hujan yang membuat banyak wilayah yang terendam banjir ketika hujan karena kurangnya wilayah resapan air.     Kata Kunci:   Perencanaan Pembangunan; Ruang Terbuka Hijau; Regulasi